Restos vegetales del sitio arqueológico Casa Vieja, Callango (Ica) - Roque, José (2003)
A paleoethnobotanical study was carried out at the Middle Horizon archaeological site of Casa Vieja, located in Callango within the Lower Ica Valley. A total of 23 species were identified, all determined to be of the Magnoliopyta Division, 78 % (or 18 species) were Magnoliopsid and 22% (or 15 species) Liliopsid. The Fabaceae are the best represented family with 6 species. Most of the analyzed samples correspond to seeds of Gossypium barbadense “cotton”. Seventy percent of the species were probably used as food; 48% for artifact-making and construction and 52% for medicinal and curative purposes.